2019
DOI: 10.1002/btpr.2952
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐conjugated PEGylated PAMAM as an efficient nanocarrier for plasmid encoding interleukin‐12 immunogene delivery toward colon cancer cells

Abstract: IL‐12 is a pleiotropic cytokine, which shows an ideal applicant for tumor immunotherapy, because of its features of creating an interconnection between innate (NK cells) and adaptive (cytotoxic T lymphocyte) immunity. IL‐12 gene therapy is a useful technique to deliver an immune‐modulatory gene directly into tumor site thereby limiting the adverse effects of systemic administration of IL‐12 proteins. One of the most largely investigated non‐viral gene carriers is polyamidoamine (PAMAM). In the current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The results of GFP transfection showed that PA‐Al and PA‐Al‐Pe at all studied C/P ratios revealed significant improvement in the efficiency of transfection, compared to PAMAM and PA‐Pe. In previous studies, hydrophobic modifications of PAMAM dendrimers resulted in improved delivery which may mainly be due to hydrophobic–hydrophilic balance in the structure of denderimer 2,31 …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The results of GFP transfection showed that PA‐Al and PA‐Al‐Pe at all studied C/P ratios revealed significant improvement in the efficiency of transfection, compared to PAMAM and PA‐Pe. In previous studies, hydrophobic modifications of PAMAM dendrimers resulted in improved delivery which may mainly be due to hydrophobic–hydrophilic balance in the structure of denderimer 2,31 …”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, hydrophobic modifications of PAMAM dendrimers resulted in improved delivery which may mainly be due to hydrophobichydrophilic balance in the structure of denderimer. 2,31 Different types of peptides, including cell-penetrating peptides (CPP), cationic peptides, amphiphilic peptides and fusogenetic peptides are currently being used in gene transfer systems. Compared to proteins, peptides are more attractive for gene delivery purposes, due to the cost-effectiveness, smaller size, and lower immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dendrimers have a variety of applications in biomedicine such as being used as carriers of drugs and genes, 27,28 as well as imaging and diagnostic agents. Therefore, dendrimers have to fulfill certain biological demands including high safety, negligible immunogenicity, being able to pass through barriers such as the blood–tissue barrier and cell membranes, high clinical efficiency due to prolonged stability in circulation, and being targetable toward specific cells and tissues 29–32 .…”
Section: Introductionmentioning
confidence: 99%